Effect of high content filling jute fiber with large aspect ratio on structure and properties of PLA composite. Issue 3 (23rd December 2021) - Na, Haining; Huang, Juncheng; Xu, Hongguang; Bao, Xin; Xie, Liangke; Liu, Fei; Zhu, Baoqing; Wang, Jiuchen; Zhu, Jin
Abstract: Jute fiber with high content and large aspect ratio is directly used to prepare PLA composites to show the effect on structure and properties. By comparing with bamboo powder, it is found that the large aspect ratio of jute fiber is helpful to form a crisscross structure in PLA composites to provide a strong framework. And the larger amount of jute fiber leads to the stronger framework in the PLA composites. Accordingly, the high comprehensive mechanical properties are produced of the PLA composites with jute fiber. Only through the simple blending of 70% jute fiber and PLA, the flexural strength and flexural modulus respectively reach 94.0 ± 4.4 MPa and 9116.7 ± 127.2 MPa, which obviously exceed the mechanical properties of PLA/bamboo blends. The addition of jute fiber also improves the thermal resistance of PLA composites as well as the crystallization ability and perfection of PLA. All the results exhibit the advantages of high content filling of jute fiber with large aspect ratio to modify PLA. Utilization of biomass filler with high content and large aspect ratio will provide an important methodology to expand the application capacity of fully degradable composites in many areas. Abstract : Jute fiber with high content and large aspect ratio is directly used to prepare PLA composites. Accordingly, a crisscross structure is formed in PLA composites to provide a strong framework. With the addition of 70% jute fiber in PLA composite, the flexural strength and flexural modulus respectively reach 94.0 ± 4.4 MPa and 9116.7 ± 127.2 MPa.